A Review Study to Investigate the Tracking of Biomedical Waste during Covid-19 Pandemic in India. Issue 1 (2nd January 2023) - Saini, Garima; Budhwar, Vikas; Choudhary, Manjusha
Abstract: The aim of this review article is planning to collect, transport, processing and dispose of hazardous and non-hazardous biomedical waste, with a special concern on the biomedical waste tracking system in India. This review article sheds insight on some of the tracking systems of COVID-19 waste over the barcode, IoT, and GPS-based trash monitoring, related to COVID-19 waste management. Better waste management may reduce the amount of time that garbage is exposed to the environment and the risk of transportation. COVID-19 waste treatment facility might assist to reduce the risk of coronavirus transmission, as well as the hazardous component risk respectively.